0
$\begingroup$

can any one show the steps how I convert the summation to norm as below: $$ \sum_{j=1}^{M'} \big(\lambda_j (\mathbf{L}\mathbf{x})^2_j\big) = \|\mathbf{L}_\lambda \mathbf{x}\|^2, \qquad\text{where } \mathbf{L}_\lambda = \mathbf{\Lambda}^{1/2}\mathbf{L} \text{ and } \mathbf{\Lambda} = \mathrm{diag}(\lambda). $$ where $L$ is a matrix, and $x$ is a vector.

$\endgroup$
  • 1
    $\begingroup$ you can also do it the other way around; just use the definition of the vector 2-norm and that of the matrix-vector product to arrive at the sum on the LHS. this does not quite fall under "computational science" ... is it perhaps a homework problem? if so you should label it as such. $\endgroup$ – GoHokies May 18 '17 at 13:48
1
$\begingroup$

Define $u_j = (L\boldsymbol{x})_j$. Then we can do the following:

\begin{align} \sum_{j=1}^{n} \lambda_j u_j^2 &= \sum_{j=1}^{n} (\lambda_j^{1/2} u_j)^2 \\ &= (\Lambda^{1/2}\boldsymbol{u})^{T}(\Lambda^{1/2}\boldsymbol{u}) \\ &= \left\lVert \Lambda^{1/2}\boldsymbol{u} \right\rVert^2 \\ &= \left\lVert \Lambda^{1/2}L\boldsymbol{x} \right\rVert^2 \\ &= \left\lVert L_{\lambda}\boldsymbol{x} \right\rVert^2 \end{align}

where, as you put it, $L_{\lambda} = \Lambda^{1/2}L$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.